2018
DOI: 10.1590/0074-02760180162
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of eukaryotic initiation factor 5A (eIF5A) affects susceptibility to benznidazole in Trypanosoma cruzi populations

Abstract: Eukaryotic initiation factor 5A (eIF5A) is a conserved protein with an essential role in translation elongation. Using one and two-dimensional western blotting, we showed that the eIF5A protein level was 2-fold lower in benznidazole (BZ)-resistant (BZR and 17LER) Trypanosoma cruzi populations than in their respective susceptible counterparts (BZS and 17WTS). To confirm the role of eIF5A in BZ resistance, we transfected BZS and 17WTS with the wild-type eIF5A or mutant eIF5A-S2A (in which serine 2 was replaced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…The metabolites of Bz can also affect the metabolism of the protozoan, enhancing its trypanocidal effect without acting in a lytic way. (31,32) Together, our results suggest that drug screening against GFP-expressing T. cruzi epimastigotes should be carefully evaluated to avoid potential errors. Although epimastigotes (insect forms) are easily cultured in laboratory conditions, these forms are not found in the mammalian hosts.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The metabolites of Bz can also affect the metabolism of the protozoan, enhancing its trypanocidal effect without acting in a lytic way. (31,32) Together, our results suggest that drug screening against GFP-expressing T. cruzi epimastigotes should be carefully evaluated to avoid potential errors. Although epimastigotes (insect forms) are easily cultured in laboratory conditions, these forms are not found in the mammalian hosts.…”
Section: Discussionmentioning
confidence: 81%
“…The metabolites of Bz can also affect the metabolism of the protozoan, enhancing its trypanocidal effect without acting in a lytic way. 31 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also shown that eIF5A protein levels were twofold lower in BZ-resistant T. cruzi populations. In addition, mutant parasites that overexpress eIF5A are three to five times more susceptible to BZ [ 56 ]. Among the categories enriched in the upregulated transcripts in the BZ-resistant T. cruzi population, translation, aromatic amino acid metabolism and arginine metabolic processes were observed among the categories enriched in the upregulated transcripts in the BZ-resistant T. cruzi population.…”
Section: Discussionmentioning
confidence: 99%
“…N-(2-amino2-hyroxymethyl) lysine, also called hypusine, is found in two eukaryotic proteins, eukaryotic translation initiation factor (eIF)-5A1 and eIF5A2 [ 121 ]. eIF5A is responsible for cell cycle regulation, apoptosis, translation, elongation, and termination [ 122 ]. The post-translational modification leads to the binding of hypusine with lysine residues of eIF5A proteins by the transfer of 4-aminobutyl moiety from spermidine to the lysine chain, which is aided by the enzymes deoxyhypusine synthase (DHPS) and deoxyhypusine hydroxylase (DOHH), also known as hypusination [ 123 ].…”
Section: Leishmaniasis and Chagas Diseasementioning
confidence: 99%